Guidelines for equitable and sustainable non-timber forest product management - Jalonen, R.; Lamers, H.; Elias, Marlène (Bioversity International, 2018)
How can we improve local livelihoods while maintaining forest biodiversity and strengthening sustainable forest management in a socially inclusive and just manner? These guidelines present practical strategies and field examples for the inclusive and sustainable extraction, sale and management of forest products, particularly NTFPs. They build upon the framework of the Community Biodiversity Management approach in which three outcomes are sought; (1) community empowerment and social equity, (2) biodiversity conservation and (3) livelihood development (Sthapit et al. 2016). The guidelines draw upon data from the project: ‘Innovations in Ecosystem Management and Conservation’ carried out between 2014 and 2017 in districts of two Indian states: Mandla District in Madhya Pradesh and Uttara Kannada District in Karnataka.